The Use of Three-Level Guide Strategy in Teaching English Narrative Text: A Classroom-Based Research - Dewi Furwana; Andi Tenrisanna Syam; St. Hartina (Research And Innovation In Language Learning (RILL), 2021)
The researcher intended to find out and describe the application of the three-level guide strategy in increasing the students reading skill of narrative text. Through classroom based research, the researcher had conducted nine meetings for three cycles. The participant of this research was the seventh grade students of junior high school. 33 students of VII-2 class were involved in this research, the researcher used observations and objective tests as her instrument. The data were collected and analyzed qualitatively and quantitatively. The researcher calculated the quantitative data from tests in each cycle through Microsoft excel. The researcher used classroom observation checklist to find out the students participation in learning. There was no improvement in students reading test scores in cycles 1 and 2. However, in cycle 3, students' reading test scores increased. In cycle I the students average score was 48.78, the students average score in cycle II was 58.28, and in the last cycle, the average score was 73.4. The researcher reveals that the three-level reading guide strategy increases students reading skills. This research is useful for teachers, students, and further researchers.